Ethics of feminist lawyering in Turkey - Kalem, Seda (Edward Elgar Publishing Ltd., 2025)
The issue of how a lawyer is expected to behave in professional affairs is significant given that defense is an integral part of the judiciary, and the legal profession has historically held a monopoly on it. In line with this structure, the profession has also been assigned a public responsibility, mostly framed around the ideals of social justice. However, professional ethics must also be considered in light of the political and ideological motivations of activist lawyers, particularly in authoritarian contexts, where judicial misconduct is on the rise and public confidence in the rule of law is eroding. Feminist lawyers, as activist practitioners, mobilize their legal skills and knowledge not only for their individual clients but also for the broader cause of gender equality. As a result, their professional conduct is often guided by a more comprehensive set of principles, which may not always be covered by the formal ethical guidelines of the legal profession. This chapter will explore how feminist lawyers in Turkey define the ethical framework for their professional activities in cases involving women clients, and how this framework is primarily shaped by their commitment to feminist principles and methods. © The Editors and Contributors Severally 2025.
Keywords: Activist Lawyering; Feminist Lawyering; Feminist Legal Ethics; Legal Ethics; Turkey